Migrant Hospitalities in the Mediterranean Encounters with Alterity in Birth and Death - Grotti, Vanessa; Brightman, Marc (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
"This book offers a fresh view on hospitality, inviting us to rethink and rearticulate decades-long debates on migration and hospitality." -Nataša Gregorič Bon, Assistant Professor of Anthropology, Research Centre SAZU, Slovenia "This tour de force of transversal analysis, comparison, and reflection exposes the double bind of hospitality. Leaving no assumption unexamined, the authors have made the anthropology of hospitality, the ethnography of migration dynamics in the Mediterranean, and transregional scalar processes shine in each other's light." -Naor Ben-Yehoyada, Assistant Professor of Anthropology, Columbia University, USA "This book addresses the pressing need for more research on hospitality and hospitality practices, a need that has become more pronounced at the end of a decade characterised by increasingly polarised debates on irregular migration and border control. A welcome addition, both for its conceptually sophisticated approach to hospitality and for its empirically rich, ethnographically grounded case studies." -Daniela DeBono, Associate Professor of International Migration and Ethnic Relations, Malmö University, Sweden This open access book applies insights from the anthropology of hospitality to illuminate ethnographic accounts of migrant reception in various parts of the Mediterranean. The contributors ground the idea and practice of hospitality in concrete ethnographic settings and challenge how the casual usage of Derridean or Kantian notions of hospitality can blur the boundaries between social scales and between metaphor and practice. Host-guest relations are multiplied through pregnancy and childbirth, and new forms of hospitality emerge with the need to offer mortuary practices for dead strangers, helping to illuminate the spatial and scalar dimensions of morality and politics in Mediterranean migrant reception. Vanessa Grotti is Associate Professor of Anthropology at the Department of Cultural Heritage, University of Bologna, Italy. Marc Brightman is Professor of Anthropology at the Department of Cultural Heritage, University of Bologna, Italy.